Promises decide - McCarty, Sarah (Jove, 2018)
As Jackson Montgomery heads home after collecting on a particularly difficult bounty, he's looking forward to a good meal, stiff drink, and maybe some female companionship. But when he sees signs of life in a house infamous for its second-rate construction, he can't resist taking a gander at who'd been fool enough to buy the disaster. He expects to find a tenderfoot for sure. He's not far off. Mimi Banfield thought she was done for when she fell into a well filled with rattlers, until a man shows up with the golden curls of an angel to rescue her. Jackson has all the survival skills she's missing and he's just the man to show her how to survive out West. As the newly minted guardian of three orphans, she could certainly use a hand. He seamlessly transitions into life with Mimi and the children, not knowing that she has a deadly secret. By the time she confesses, it may just be too late for salvation.